PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA KOMISI PEMILIHAN UMUM (KPU) DI PROVINSI SUMATERA UTARA - Padang, Novi Natalia; Padang, Wendi Suprapto; Gultom, Lamtiur Lidia (UNIKA Santo Thomas, 2025)
This study aims to determine and analyze how accountability and transparency affect the quality of financial reports at the General Election Commission in North Sumatra. The population used in this study is the KPU in North Sumatra. The data analysis technique used in the study is by using PLS-SEM for quantitative analysis. The results of this study indicate that transparency and accountability have a positive and significant effect on the quality of financial reports.